Peningkatan Keterampilan Kognitif pada Anak Autis Usia Dini Melalui Media Visual Interaktif - Nugrahani, Rahina; Sihombing, Riama Maslan; Idris, Muhammad Zaffwan bin; Windiarti, Rina; Diana, Diana (Jurnal Sosioteknologi, 2024)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition characterized by impairments in social communication, restricted interests, and repetitive behaviors. Children with ASD often face challenges in the development of cognitive skills, which play a crucial role in academic achievement, adaptive functioning, and overall quality of life. This study introduces an innovative approach to aid early childhood individuals diagnosed with ASD in recognizing their daily routines by means of a visual interactive board game. The developed visual interactive board game, although the design is simple, is meticulously structured to foster and enhance cognitive skills, specifically focusing on language development and improvement in adaptive behavior. The efficacy of this medium was examined through a single-case method utilizing the Single Subject Research (SSR) experimental approach. The research involved three children aged 4-5 years with an ASD diagnosis, employing a patterned B1-I-B2 design. The results of this study underline the potential of interactive board games as an engaging tool for fostering cognitive skills in early childhood autism.